Estudo da influência do material pulverulento nas propriedades físicas e mecânicas na argamassa estabilizada - Leandro Damião dos Santos (2020)
The companies that are part of the construction industry have been looking every day for ways that provide productive sustainability. Thus, the supply area has been extensively explored for developing suppliers of inputs that have innovative products and ensure efficiency, quality and competitiveness in the market. Thus, the use of industrialized mortars, specifically stabilized ones, has still generated some questions for both consumers and manufacturers, especially with regard to the formulation and performance of the product in relation to the coating system. Therefore, this work aims to verify, experimentally, a study regarding the influence of the presence of powdery material from a sample of gneiss sand, with three variations of contents (0, 15 and 30%) in substitution in mass of the sand. And using a reference sand sample, being analyzed the performance of the mortar stabilized for 24 hours, in its physical and mechanical properties in the fresh and hardened state. Through laboratory tests, the properties of: consistency index, water retention index, air incorporation content, density of fresh and hardened mass; as well as mechanical resistance to compression and traction in flexion. Therefore, in view of the results obtained, it was possible to verify that both the excess of powdery sand material and its absence, directly affects the properties of the mixture and the performance of the stabilized mortar. The best results are obtained in samples with a limit of powdery material between 12 to 15%.